Comisión de Enseñanza Secundaria y de Pregrado Acta 4 - Carranza, Raquel; Franchi, Nicolás Orlando; Gangoso, Zulma; Guerra, Aldo; Guzmán, Claudia; Lombroni, Fernando; Manzotti, Marcelo; Molina, Stella; Soisa, Cecilia; Spadiliero De Lutri, Mirta (Universidad Nacional de Córdoba, 2019)
Fil: Carranza, Raquel. Universidad Nacional de Córdoba; Argentina.